2016
DOI: 10.1149/2.0711603jes
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Evolution during the Corrosion of Galvanically Coupled Magnesium

Abstract: In this study, the impact of galvanic coupling of magnesium to steel on the corrosion rate, surface morphology, and surface film formation was investigated. In particular, experiments were performed to examine and quantify the role of self-corrosion (also called negative difference effect (NDE) or anodic hydrogen) during the corrosion of galvanically coupled Mg. It was found that galvanic coupling at high cathode-to-anode area ratios resulted in high rates of corrosion that impacted hydrogen evolution on the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Initially the corrosion rate is fast, but with increasing amount of added Na 2 B 4 O 7 evolved H 2 decreases, that is, the corrosion rate decreases. These results are in conformity with the literature results [32,33].…”
Section: Resultssupporting
confidence: 94%
“…Initially the corrosion rate is fast, but with increasing amount of added Na 2 B 4 O 7 evolved H 2 decreases, that is, the corrosion rate decreases. These results are in conformity with the literature results [32,33].…”
Section: Resultssupporting
confidence: 94%
“…The hydrogen evolution observed in cathodic branches was enhanced for the electrolytes containing ethanol. It was reported the effects of hydrogen absorbed on metal surfaces on anodic polarization in several aspects including retarding the formation of passivating film, changing the condition of electrode surface, decreasing the resistance toward charge transfer and ion diffusion, and increasing the capacitance 37 , 38 .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the corrosion of magnesium includes self-corrosion and galvanic corrosion. It was reported that during galvanic corrosion, the surface morphology was dramatically different from the filiform structures associated with free corrosion 30 . In this study, the SEM demonstrated the change of surface morphology, indicating the galvanic-like corrosion.…”
Section: Discussionmentioning
confidence: 97%